An examination of the legal and religious dimensions to separation in marriage (2021)
Separation in marriage has become a burning issue that has generated a lot of debates in Nigeria today as it affects many homes and the society at large. Scholars in Order to deal with the problem have approached the subject matter from the cultural, psychological, and sociological perspectives. 13ut, an area where little or no attention has been paid over the years which necessitated this study is the religious and legal dimensions to the discourse. That is, a religious and legal look at what constitutes Separation in marriage and how the menace can be brought to the barest minimum. The method adopted in the study is the use of materials that are relevant to Separation and divorce. Recommendation will be made on how to address the issues involved in Separation and how separated couples can live a better life thereby enhancing peace and harmonious relationship in the society.